Depletion of β-sitosterol and enrichment of quercetin and rutin in Cissus quadrangularis Linn fraction enhanced osteogenic but reduced osteoclastogenic marker expression - Jetsada Ruangsuriya; Suporn Charumanee; Supat Jiranusornkul; Panee Sirisa-ard; Busaban Sirithunyalug; Jakkapan Sirithunyalug; Thanawat Pattananandecha; Chalermpong Saenjum (BMC, 2020)
Abstract Background Cissus quadrangularis Linn. (CQ) has been used in Indian and Thai traditional medicine for healing bone fractures because of numerous active ingredients in CQ. It is still unclear which compounds are the active ingredients for bone formation. Methods The molecular docking technique, the ethanolic extraction along with hexane fractionation, and an in vitro experiment with a human osteoblast cell line (MG-63) were used to narrow down the active compounds, to prepare the CQ extract, and to test biological activities, respectively. Results The molecular docking technique revealed that quercetin and β-sitosterol had highest and lowest potential to bind to estrogen receptors, respectively. Compared to the crude ethanol extract (P1), the ethanolic fraction (P2) was enriched with rutin and quercetin at 65.36 ± 0.75 and 1.06 ± 0.12 mg/g, respectively. Alkaline phosphatase (ALP) activity was significantly enhanced in osteoblasts exposed to the P2 in both tested concentrations. The amount of hydroxyproline was slightly increased in the P1 treatment, while osteocalcin was inhibited. Moreover, the P2 significantly activated osteoprotegerin (OPG) and inhibited receptor activator of nuclear factor κ ligand (RANKL) expression. Conclusions Taken together, the enriched rutin and quercetin fraction of CQ triggered the molecules involved in bone formation and the molecules inhibiting bone resorption.